(untitled) - Harries, Meirion (London, 1987)
The first of a projected four-volume history of Japan entitled The Sun Incandescent, Sheatbing the Sword traces Japanese history from the American post-war Occupation to the present day, focusing on the rise and fall of Japanese militarism in the four decades since.
Keywords: Militarism,Japan; History,History,Allied occupation, 1945-1952; Japan